The Mechanical Properties of a Wall-Climbing Caterpillar Robot: Analysis and Experiment. (14th January 2013) - Wang, Kun; Wang, Wei; Zhang, Houxiang
This paper builds the kinematic model of a wall-climbing caterpillar robot to reveal the validity and the benefits of the closed-chain kinematics of the four-linkage mechanism to a crawling gait. The caterpillar robot can climb on a vertical wall by coordinating the rotations of one active joint and three passive joints. The mechanical property of the closed-chain kinematics of the four-linkage model is analysed. Furthermore, the relation between the driving joint torque and joint angle in the wall-climbing process is deduced based on the coplanar arbitrary force system. Afterwards, the joint control method is discussed in order to coordinate the rotation of the four joints so as to realize a reasonable wall climbing gait. To testify to the availability of the closed-chain four-linkage model, a wall-climbing caterpillar robot is developed with three different adhesion modules based on the vibrating suction method. A successful wall-climbing test confirms both the practicality of the four-linkage model and the validity of the adhesion modules based on the vibrating suction method. The results also show the reasonableness of the driving joint selection rule for ensuring a safe and reliable wall-climbing procedure.